Chinese aquaculture in light of green growth - Leilei Zou; Shuolin Huang (Aquaculture Reports, 2015)
Over China’s long history of aquaculture development, great achievements have been made by enhancing aquaculture as the major contributor to aquatic products supply, while lessons have also been learnt that aquaculture has been developing at the cost of environment. Priority is now given to the aquaculture development in the light of green growth, which attaches importance to both environment protection and high productivity. To sustain Chinese aquaculture in a green-growth manner, polices changes have been made, a comprehensive legal framework has been developed, and an organized institutional framework has been set up. The extension of science and technology also serves as the back-up for green growth in Chinese aquaculture. Chinese aquaculture is still confronted with various challenges, while green growth will be the key to a more responsible and prosperous aquaculture industry in China.